ҚАРАҚАЛПАҚ СПОРТ ТЕРМИНОЛОГИЯСЫНДА ШЕТ ТИЛ ӨЗЛЕСТИРМЕЛЕРИНИҢ ҚОЛЛАНЫЛЫЎЫ ҲАҚҚЫНДА - Кощанов, К.М.; Мураткамалова, Р.Ж. (SCIENCE and SOCIETY, 2021)
The article deals with the use of borrowed sports terms in the Karakalpak Language.
Keywords: sport; physical; the Olympic Games; coach (trainer) box; champion; competition; school; college